2014
DOI: 10.1177/1753193414562706
|View full text |Cite
|
Sign up to set email alerts
|

Fracture-dislocations of the carpometacarpal joints of the ring and little finger

Abstract: We report the functional and radiographic results of 16 patients with fracture-dislocations of the ring and little finger carpometacarpal joints and 23 cases with fracture-dislocations of only the little finger carpometacarpal joint treated between 2006 and 2012. The above two cohort populations of patients were treated with either open reduction and pin fixation or closed reduction and pin fixation. These patients were followed for a mean of 13 months (range 9 to 48). The DASH scores for patients with fractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 20 publications
1
24
0
1
Order By: Relevance
“…Management was only briefly covered as other aspects of the care pathway were also considered. The conclusion that operative management is required to treat fifth CMCJ injuries appears in line with current practice given that more severe injuries were often treated operatively in most of the studies included in our review (Frick et al, 2011;Gehrmann et al, 2015;Kjaer-Petersen et al, 1992;Schortinghuis and Klasen, 1997). However, the present systematic review has demonstrated that this is not evidence-based.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Management was only briefly covered as other aspects of the care pathway were also considered. The conclusion that operative management is required to treat fifth CMCJ injuries appears in line with current practice given that more severe injuries were often treated operatively in most of the studies included in our review (Frick et al, 2011;Gehrmann et al, 2015;Kjaer-Petersen et al, 1992;Schortinghuis and Klasen, 1997). However, the present systematic review has demonstrated that this is not evidence-based.…”
Section: Discussionsupporting
confidence: 73%
“…No trials of fifth CMCJ injury were identified on the UKCRC Registered Clinical Trials Unit Network. Three other studies were added after reviewing the reference lists of the final articles, from which two were included (Gehrmann et al., 2015; Lawlis and Gunther, 1991). During manual screening for duplicates, a further eight studies were removed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bei den axialen Luxationen und Luxationsfrakturen können wiederum ulnare und radiale Peri-und transtrapezoidale Luxationen kommen sehr selten vor und bisher sind nur wenige Fallberichte in der Literatur beschrieben [2][3][4]. Insgesamt sind Verletzungen der distalen Handwurzelreihe aufgrund biomechanischer Besonderheiten deutlich seltener, als die der proximalen Reihe [5] und liegen meist als Begleitverletzung karpometakarpaler Luxationsfrakturen vor [6][7][8][9][10]. Verletzungen des Os trapezoideum werden als Folge schwerer Distorsions-, Stauchungs-und Quetschtraumata beobachtet [2].…”
Section: Introductionunclassified